Learning from Excellence: the 'Yaytix' programme. Issue 4 (November 2018) - Chain, Gabriel; Marshall, Emma; Geddie, Cathy; Joseph, Sonia; Chain, Benjamin; Clark, Claire
Background and aims: Learning from error can have a negative impact on the staff involved in the error ('second victim phenomenon' 1 ). We created a project, based on the principles of the Learning from Excellence project, 2 to learn from excellence and correct the imbalance of negative to positive feedback in the context of hospital practice. Methods and results: Using a questionnaire, we surveyed staff on existing feedback mechanisms and morale. We then introduced a system where staff recorded and commented on examples of excellence in practice. Recipients and their supervisors received copies of these reports and the feedback was analysed and discussed with senior staff (consultant, senior charge nurse, managers). We re-audited the staff two months after starting this project and noted improvements in staff morale and in positive reporting. Conclusions: This project has improved the process of giving and learning from positive feedback and had a significant impact on staff morale. We can also demonstrate an example of improved clinical practice (from feedback received) and will now attempt to measure clinical outcomes with a new prospective study. Finally, we hope to set up a regional programme of reporting excellence in South-East Scotland.